On the significance of disciplinary variation in research articles: Perspectives from nominalization - Zhila Heidari Kaidan; Alireza Jalilifar; Alexanne Don (Cogent Education, 2021)
The present study explored nominalization use in a sample of research articles (RAs) of various types in physics and applied linguistics. To this end, 134 RAs from the related journals of these disciplines were carefully selected and studied to identify occurrences ofnominalization. Results indicated that the authors in applied linguistics significantly used more nominalization than their counterparts in physics. Moreover, the analysis brought out the findings that the deployment of nominalization Type Two (i.e., processes) is significantly different from the other three types of nominalization in each discipline. Further analysis showed no significant difference among various types of RAs regarding nominalization use in physics contrary to applied linguistics. In applied linguistics, one striking result emerging from the study was the frequent use of nominalization in experimental RAs. In addition, the study suggested 15 patterns of nominalization in the empirical RAs of the two disciplines. Of these, the RAs demonstrated distinct trends in using four patterns. This study has important implications in reference to academic writing teachers and course designers.